2015
DOI: 10.21273/hortsci.50.9.1332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Grafted Watermelon for Verticillium Wilt Severity, Yield, and Fruit Quality in Washington State

Abstract: Verticillium wilt caused by Verticillium dahliae is a serious disease for watermelon growers in Washington State. Grafting represents a possible alternative disease management strategy, but little is known about rootstock resistance to verticillium wilt or the performance of grafted watermelon in the different production regions of the state. In this study, verticillium wilt severity, yield, and fruit quality were evaluated at three contrasting field sites in Washington using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 25 publications
8
33
0
Order By: Relevance
“…Experimental controls consisted of two commercial cultivars, rootstock cv. Tetsukabuto (C. maxima · C. moschata) (American Takii, Inc., Salinas, CA) as the verticillium wilt-resistant control (Wimer et al, 2015a) and diploid (seeded) watermelon cv. Sugar Baby (Osborne Quality Seeds, Mount Vernon, WA) as the verticillium wilt-susceptible control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental controls consisted of two commercial cultivars, rootstock cv. Tetsukabuto (C. maxima · C. moschata) (American Takii, Inc., Salinas, CA) as the verticillium wilt-resistant control (Wimer et al, 2015a) and diploid (seeded) watermelon cv. Sugar Baby (Osborne Quality Seeds, Mount Vernon, WA) as the verticillium wilt-susceptible control.…”
Section: Methodsmentioning
confidence: 99%
“…Grafting compatibility can be defined as the successful union of the rootstock and scion in a manner that does not compromise fruit yield and quality. Previous studies have found that yield of watermelon grafted onto interspecific Cucurbita hybrids and L. siceraria can be equivalent to or greater than that of nongrafted watermelon (Bekhradi et al, 2011;Paroussi et al, 2007;Wimer et al, 2015a). Yetıs xır et al (2003) also reported that watermelon grafted onto L. siceraria produced higher yield than Cucurbita hybrids.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…14 In a recent study in the northwestern USA, grafting did not affect SSC and lycopene content of fruit from seeded, diploid watermelon 'Sugar Baby' grafted onto Cucurbita maxima × C. moschata rootstocks. 18 However, in another study conducted in Greece, fruit from grafted seeded, diploid watermelon cultivars with C. maxima × C. moschata rootstocks demonstrated a potential delay in pre-harvest accumulation of sucrose while achieving higher lycopene content and improved flesh color during postharvest. 16 Grafting with the interspecific hybrid squash rootstock 'TZ148' also increased lycopene content of the seeded, diploid watermelon 'Pegasus', but the peak lycopene value of fruit from grafted plants was achieved later than in the non-grafted controls, 19 suggesting potential influence of rootstock on fruit development and ripening.…”
Section: Introductionmentioning
confidence: 96%
“…Studies of other quality factors such as soluble solids content (SSC), titratable acidity (TA) and lycopene content have produced conflicting results, most likely due to variations in environmental conditions and rootstock/scion combinations . In a recent study in the northwestern USA, grafting did not affect SSC and lycopene content of fruit from seeded, diploid watermelon ‘Sugar Baby’ grafted onto Cucurbita maxima × C. moschata rootstocks . However, in another study conducted in Greece, fruit from grafted seeded, diploid watermelon cultivars with C. maxima × C. moschata rootstocks demonstrated a potential delay in pre‐harvest accumulation of sucrose while achieving higher lycopene content and improved flesh color during postharvest .…”
Section: Introductionmentioning
confidence: 99%